Monotonicity and inequalities related to the generalized inverse Lemniscate functions - Yin, Li; Lin, Xiu Li (Revista de la Real Academia de Ciencias Exactas, Físicas y Naturales. Serie A, Matemáticas, 2022)
In the paper, we mainly studied the monotonicity and inequalities for some functions related to the generalized inverse lemniscate and the generalized hyperbolic inverse lemniscate functions. At first, we presented a bound estimation of the generalized inverse lemniscate functions by using Lerch Phi function. Finally, some Shafer-Fink, Wilker and Huygens type inequalities for the generalized inverse lemniscate and the generalized hyperbolic inverse lemniscate functions were obtained.